2021
DOI: 10.1016/j.clcc.2020.08.003
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Human Phase 1b Trial of Quinacrine Plus Capecitabine in Patients With Refractory Metastatic Colorectal Cancer

Abstract: Quinacrine and 5-fluorouracil (5-FU) have preclinical activity against colorectal cancer. This phase 1b clinical trial evaluated the safety and efficacy of quinacrine and the 5-FU analog capecitabine in patients with treatment-refractory metastatic CRC (mCRC). The maximally tolerated dose was determined; we observed 1 partial response and 5 stable disease. This regimen may be an option for patients with treatment-refractory mCRC. Background: Quinacrine plus a fluoropyrimidine has in vivo efficacy against metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…However, all of the patients selected for this study either had EGFR-negative adenocarcinoma or squamous cell carcinoma, which technically could limit the effects of erlotinib, as shown in various earlier phase II/III studies of erlotinib in EGFR negative and SCC patients. Another phase Ib clinical study completed this year assessed the combination of quinacrine and capecitabine in metastatic colon cancer patients (clinical trial identifier NCT01844076) [106]. Three patients showed SD and one showed PR in the dose-finding cohort of the study, while two out of the seven patients in the expansion cohort showed SD on 100 mg/kg QC.…”
Section: Clinical Research Studies Of Quinacrine In Cancer Treatmentmentioning
confidence: 99%
“…However, all of the patients selected for this study either had EGFR-negative adenocarcinoma or squamous cell carcinoma, which technically could limit the effects of erlotinib, as shown in various earlier phase II/III studies of erlotinib in EGFR negative and SCC patients. Another phase Ib clinical study completed this year assessed the combination of quinacrine and capecitabine in metastatic colon cancer patients (clinical trial identifier NCT01844076) [106]. Three patients showed SD and one showed PR in the dose-finding cohort of the study, while two out of the seven patients in the expansion cohort showed SD on 100 mg/kg QC.…”
Section: Clinical Research Studies Of Quinacrine In Cancer Treatmentmentioning
confidence: 99%
“…Quinacrine, a synthetic acridine-based anti-malarial drug, has been well studied and documented for its antineoplastic activity in numerous preclinical and clinical studies [12][13][14]. The molecular mechanisms of its anti-cancer effects have been reported to be mediated through the activation of p53 signaling, induction of autophagy, DNA and mitochondrial damage, and facilitation of interaction between TRAIL and death receptor DR5 [15][16][17][18].…”
Section: Introduction:-mentioning
confidence: 99%
“…Recently, Qx has been tested in several cancer trials (NCT01839955, NCT00417274, NCT01844076) and prion disease (NCT00183092, NCT00104663). Moreover, it was found that the maximum tolerated dose of Qx was 100 mg twice daily per 21 d in a colorectal cancer study ( 12 ).…”
mentioning
confidence: 99%